The SAGE handbook of modern Japanese studies - Babb, James (London : SAGE Publications Ltd, 2015)
This title provides a cutting edge and cross-disciplinary exploration of the broad field of Japanese studies. An international team of experts explore land, history and culture, society, medicine, the economy, and politics and foreign relations.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 12, 2015).
Keywords: Japan -- Study and teaching; Japan -- Civilization